Fecal Bacteria, Bacteriophage, and Nutrient Reductions in a Full‐Scale Denitrifying Woodchip Bioreactor. Issue 3 (1st May 2016) - Rambags, Femke; Tanner, Chris C.; Stott, Rebecca; Schipper, Louis A.
Abstract : Denitrifying bioreactors using woodchips or other slow‐release carbon sources can be an effective method for removing nitrate (NO3 − ) from wastewater and tile drainage. However, the ability of these systems to remove fecal microbes from wastewater has been largely uninvestigated. In this study, reductions in fecal indicator bacteria ( Escherichia coli ) and viruses (F‐specific RNA bacteriophage [FRNA phage]) were analyzed by monthly sampling along a longitudinal transect within a full‐scale denitrifying woodchip bioreactor receiving secondary‐treated septic tank effluent. Nitrogen, phosphorus, 5‐d carbonaceous biochemical oxygen demand (CBOD5 ), and total suspended solids (TSS) reduction were also assessed. The bioreactor demonstrated consistent and substantial reduction of E. coli (2.9 log10 reduction) and FRNA phage (3.9 log10 reduction) despite receiving highly fluctuating inflow concentrations [up to 3.5 × 10 5 MPN (100 mL) −1 and 1.1 × 10 5 plaque‐forming units (100 mL) −1, respectively]. Most of the removal of fecal microbial contaminants occurred within the first meter of the system (1.4 log10 reduction for E. coli ; 1.8 log10 reduction for FRNA phage). The system was also efficient at removing NO3 − (>99.9% reduction) and TSS (89% reduction). There was no evidence of consistent removal of ammonium, organic nitrogen, or phosphorus. Leaching of CBOD5 occurred during initial operation but decreased and stabilized at lower values (14 g O2 m −3 ) after 9 mo. We present strong evidence for reliable microbial contaminant removal in denitrifying bioreactors, demonstrating their broader versatility for wastewater treatment. Research on the removal mechanisms of microbial contaminants in these systems, together with the assessment of longevity of removal, is warranted. Core Ideas: Denitrifying bioreactors are a technology for nitrate removal from wastewater. We show a full‐scale bioreactor can also remove fecal bacteria and viruses. Fecal bacteria and viruses were reduced by >2.9 log10 . Median effluent concentration of E. coli was 20 MPN (100 mL) −1 . Median effluent concentration of F‐specific RNA phage was 3 PFU (100 mL) −1 .